Implementation of Vocational High School as a Center of Excellence through Digital Products to Develop Islamic Boarding School-Based Entrepreneurship - Shofiana, Dwi Erma; Imron; Tohirin, M. (Journal of Pedagogy and Education Science, 2025)
The rapid development of the digital era demands that vocational schools not only prepare graduates with technical skills but also foster creative, character-based, and competitive entrepreneurial competencies, especially in Islamic boarding school–based institutions. This research aims to determine the implementation, forms of activities, and role of implementing SMK centers of excellence through creative economy digital products to improve Islamic boarding school-based entrepreneurial competencies. The subject of this research is Syubbanul Wathon Vocational School, Magelang. This research method uses qualitative descriptives. Qualitative research data collection instruments include observation, interviews, and documentation. Data analysis was carried out through data collection, data reduction, data presentation, and verification or drawing conclusions. A credibility test with triangulation was used to check the validity of the qualitative data in this study. The research results show that the implementation of the Center for Excellence Vocational School program was successful through integrating Islamic boarding school values with the development of creative economy-based digital products. Main activities include technical and non-technical training, such as graphic design, social media management, application development, and digital marketing. The implementation of this program plays a significant role in forming graduates who have competitive, creative, and characterful entrepreneurial competencies. This research contributes to providing a model for strengthening entrepreneurship in vocational schools by combining pesantren values and digital creative economy development. Therefore, it is recommended that similar vocational schools adopt this integrative approach to enhance graduates’ readiness in facing the digital economy era.